Bringing the Leader Back in: Why, How, and When Leadership Empowerment Behavior Shapes Coworker Conflict. Issue 5 (27th May 2020) - Adamovic, Mladen; Gahan, Peter; Olsen, Jesse E.; Harley, Bill; Healy, Joshua; Theilacker, Max
With the diffusion of team-based work organizations and flatter organizational hierarchies, many leaders empower employees to perform their work. Empowerment creates an interesting tension regarding coworker conflict, enhancing trust and giving employees more autonomy to prevent conflict, while also increasing workload and the potential for coworker conflict. Recent conflict research has focused on how characteristics of individuals, groups, and tasks contribute to conflict among coworkers. We extend this work by exploring the role of leader empowerment behavior (LEB) in influencing coworker conflict. Our model integrates research on LEB and coworker conflict to help organizations manage coworker conflict effectively. To test our model at the workplace level, we utilize data drawn from matched surveys of leaders and employees in 317 workplaces. We find that LEB relates negatively to relationship and task conflict through affective and cognitive trust in leaders. We further find that LEB relates negatively to relationship and task conflict through reduced workload, but only when employees have a clear role description. In contrast, if employees have unclear roles, LEB has a U-curve relationship with workload: a moderate level of LEB reduces workload, but a high level of LEB increases workload, in turn increasing coworker conflict. Finally, relationship conflict has a direct negative effect on task performance, whereas task conflict has an indirect negative effect through relationship conflict.